Hydro-test Method to Detect Leaks in Pressure Vessels at PT DIHI - Irawan, Muhammad Afeef Febry; Pinem, Mekro Permana; Wiyono, Slamet (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2023)
In the manufacturing of a device, several types of testing are performed. Testing must be done to ensure that the designed device is completely safe for long-term use and meets existing standards. There are several tests conducted, one of which is the Hydrotest. This Hydrotest is conducted to test whether the designed device experiences leakage, particularly at weld joints, by filling pressurized water into a test device and holding it for a certain period. In this study, we aim to conduct a Hydrotest on a Pressure Vessel to see if the designed Pressure Vessel experiences leakage in its construction. From the results of the testing conducted, it was found that the designed Pressure Vessel did not experience leakage, particularly at each weld joint. Based on the Pressure and Temperature Chart Recorder, the graph indicates that there is no pressure drop, and the temperature remains within a safe range.